SERVICE QUALITY AND CUSTOMER LOYALTY IN PEACEKEEPING MISSIONS - Azman Ismail; Mohd Helmi Ali; Ahmad Azan Ridzuan; Herwina Rosnan (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2016)
The capability of service providers to plan and implement the quality components in executing daily job may have a significant impact on customer loyalty. However, the role of service quality as an important determinant has been given less attention in the workplace quality research literature. Therefore, this study was undertaken to measure the relationship between service quality and customer loyalty. A survey method was employed to collect data from Malaysian soldiers who involved in peacekeeping missions at Middle Eastern country. The outcomes of SmartPLS path model analysis demonstrate that the ability of organization to appropriately implement tangible, reliability, responsiveness, assurance and empathy in executing daily job has been important determinants of customer loyalty. Further, this study provides discussion, implications and conclusion.